2013
DOI: 10.4306/pi.2013.10.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Quantitative Electroencephalogram Findings between Adjustment Disorder and Major Depressive Disorder

Abstract: ObjectiveAdjustment disorder (ADJ) is a common diagnosis. However, it is difficult to distinguish ADJ from other major Axis I disorders, such as major depressive disorder (MDD). The aim of this study was to determine the distinguishing neurophysiological characteristics between ADJ and MDD using quantitative analysis of an electroencephalogram (QEEG).MethodsThe study included 30 patients with ADJ and 51 patients with MDD. Resting (eye closed) vigilance controlled EEG recordings were assessed at 19 electrode si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…44 Still, most consistently, connectivity differences between patients and controls were found within the EEG alpha band. 11,15,16,45 These findings paved the way to the hypothesis of a predictive value of EEG alpha band connectivity patterns in treatment of MDD by ECT.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…44 Still, most consistently, connectivity differences between patients and controls were found within the EEG alpha band. 11,15,16,45 These findings paved the way to the hypothesis of a predictive value of EEG alpha band connectivity patterns in treatment of MDD by ECT.…”
Section: Discussionmentioning
confidence: 79%
“…18 Thus, patterns of baseline EEG connectivity mirror the wired network within the brain that is the direct target of ECT via electrical stimulation, thus making EEG an optimal tool for treatment prediction. 49 Still, it is very intriguing that some works of EEG connectivity profiles in MDD report of increased alpha connectivity in comparison with healthy controls 16,45 with decreasing alpha connectivity during successful drug treatment in patient subgroups. 18 In this study, a decreased alpha connectivity at baseline was found as being predictive for response to ECT.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies used a huge variety of connectivity measures like partial directed coherence, Granger causality, structural synchrony index and phase synchrony index. Some found decreased EEG connectivity in MDD [122,132,133,134] while others report of increased EEG connectivity in MDD, mainly in the alpha band [135,136,137,138]. More studies are needed to disentangle the complex relationship between the different connectivity measures and their physiological interpretation and to estimate the value for treatment prediction.…”
Section: Biomarkersmentioning
confidence: 99%
“…Finding objective, biological, differences between these disorders could give important insights in relation to pathophysiology and classification. Electroencephalography is one commonly used method for this purpose, 3 another is recording of motor activity. Alterations of motor activity are prominent features in several psychiatric disorders, such as ADHD, 4 mood disorders and schizophrenia, 5 6 with the most pronounced disturbances seen in the catatonia.…”
Section: Introductionmentioning
confidence: 99%